Hb S/β-Thalassemia in the REDS-III Brazil Sickle Cell Disease Cohort: Clinical, Laboratory and Molecular Characteristics. (2nd January 2020) - Belisário, André R.; Carneiro-Proietti, Anna B.; Sabino, Ester Cerdeira; Araújo, Aderson; Loureiro, Paula; Máximo, Cláudia; Flor-Park, Miriam V.; Rodrigues, Daniela D.O.W.; Ozahata, Mina Cintho; McClure, Christopher; Mota, Rosimere Afonso; Gomes Moura, Isabel C.; et al.
Abstract: We described the clinical, laboratory and molecular characteristics of individuals with Hb S ( HBB : c.20A>T)/β-thalassemia (Hb S/β-thal) participating in the Recipient Epidemiology and Donor Evaluation Study (REDS-III) Brazil Sickle Cell Disease cohort. HBB gene sequencing was performed to genotype each β-thal mutation. Patients were classified as Hb S/β 0 -thal, Hb S/β + -thal-severe or Hb S/β + -thal based on prior literature and databases of hemoglobin (Hb) variants. Characteristics of patients with each β-thal mutation were described and the clinical profile of patients grouped into Hb S/β 0 -thal, Hb S/β + -thal and Hb S/β + -thal-severe were compared. Of the 2793 patients enrolled, 84 (3.0%) had Hb S/β 0 -thal and 83 (3.0%) had Hb S/β + -thal; 40/83 (48.2%) patients with Hb S/β + -thal had mutations defined as severe. We identified 19 different β-thal mutations, eight Hb S/β 0 -thal, three Hb S/β + -thal-severe and eight Hb S/β + -thal. The most frequent β 0 and β + mutations were codon 39 ( HBB : c.118C>T) and IVS-I-6 (T>C) ( HBB : c.92+6T>C), respectively. Individuals with Hb S/β 0 -thal had a similar clinical and laboratory phenotype when compared to those with Hb S/β + -thal-severe. Individuals with Hb S/β + -thal-severe had significantly lower total Hb and Hb A levels and higher Hb S, white blood cell (WBC) count, platelets and hemolysis markers when compared to those with Hb S/β + -thal. Likewise, individuals with Hb S/β + -thal-severe showed a significantly higher occurrence of hospitalizations, vaso-occlusive events (VOE), acute chest syndrome (ACS), splenic sequestration, blood utilization, and hydroxyurea (HU) therapy.